A pricing model for governments' subsidy in the green supply chain. (1st January 2014) - Xu, Ai; Zhou, Zongqing
Green supply chain management has gained more attention in recent years, as a modern management method by considering economic efficiency, social and environmental impact simultaneously. In this paper, the government's subsidy in the green supply chain for home appliances industry is studied by constructing a three-player game model among governments, home appliances enterprises and consumers. Through studying the relationships and game status and analysing the equilibrium of the game model, the paper points out the necessity of creating a government's subsidy, and proposes the principles of the subsidy as well as provides a numerical example. The research results indicate that governments can improve the enthusiasm and likelihood of enterprises and consumers to participate in this model of green supply chain management by creating appropriate subsidy to the enterprises, to the consumers and by imposing penalties to those enterprises that do not participate in the green supply chain management.